Friction perception resulting from laterally vibrotactile stimuli - Imaizumi, Akihiro; Okamoto, Shogo; Yamada, Yoji (ROBOMECH journal, 2017)
When a human rubs a contactor that is vibrating laterally at 3–10 Hz with an amplitude of ~1 mm, the friction is perceived as being greater than that sensed when touching a stationary contactor. This phenomenon could be exploited for a new vibrotactile approach to friction perception; however, the principles behind it have yet to be explained. In this study, we hypothesized that the perceived friction increases because of the Stribeck characteristic and stick-slip phenomenon of friction, whereby the friction varies depending on the relative velocity between a subject’s fingertip and contactor. The relative velocity instantaneously decreases because of the lateral vibration of the contactor, while the friction rises during the same period. To test this hypothesis, we simulated the friction forces between a fingertip and a vibrating contactor. Furthermore, we performed psychophysical experiments using five participants, in which each explored a vibrating contactor and subjectively compared the perceived friction under several stimulus conditions. The simulated friction forces, the results of the psychophysical experiments, and physical observation suggested that the transient increases in friction caused by lateral vibration of the contactor influenced friction perception for a laterally vibrating contactor.